Cyclodextrin metal-organic framework as vaccine adjuvants enhances immune responses - Congcong Li; Chaoxi Chen; Yucai Wei; Min Tan; Shuo Zhai; Juebo Zhao; Lu Wang; Tao Dai (Taylor & Francis Group, 2021)
It is urgently needed to develop novel adjuvants for improving the safety and efficacy of vaccines. Metal-organic frameworks (MOFs), with high surface area, play an important role in drug delivery. With perfect biocompatibility and green preparation process, the γ-cyclodextrin metal-organic framework (γ-CD-MOF) fabricated with cyclodextrin and potassium suitable for antigen delivery. In this study, we modified γ-CD-MOF with span-85 to fabricate the SP-γ-CD-MOF as animal vaccine adjuvants. The ovalbumin (OVA) as the model antigen was encapsulated into particles to investigate the immune response. SP-γ-CD-MOF displayed excellent biocompatibility in vitro and in vivo. After immunization, SP-γ-CD-MOF loaded with OVA could induce high antigen-specific IgG titers and cytokine secretion. Meanwhile, SP-γ-CD-MOF also significantly improved the proliferation of spleen cells and activated and matured the bone marrow dendritic cells (BMDCs). The study showed the potential of SP-γ-CD-MOF in vaccine adjuvants and provided a novel idea for the development of vaccine adjuvants.